Analysis of the Utilization of TikTok as a Learning Media in Islamic Religious Education for Generation Z Students - Fachriza, Rendy; Ginting, Intan Johan Syahputri; Hikma, Durratul; Awaeputeh, Nurul Huda (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the utilization of TikTok as a learning media in Islamic Religious Education (IRE) for Generation Z students. The research method employed is a qualitative approach with a descriptive design. The research subjects include teachers and students who actively use TikTok in the learning process. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The results indicate that the use of TikTok as a learning medium can enhance students’ learning interest, engagement, and facilitate the delivery of materials in a creative and contextual manner. Short video-based content is considered effective in capturing the attention of Generation Z students, who tend to be visual and dynamic learners. However, several challenges were identified, including potential distractions, limited content control, and the need for strong digital literacy. Therefore, appropriate pedagogical strategies are required to effectively integrate TikTok into Islamic Religious Education to positively impact learning quality.